Effect of hydrogen plasma treatment on the growth and microstructures of multiwalled carbon nanotubes - Srivastava, S. K.; Vankar, V. D.; Kumar, V. (Nano-Micro Letters, 2010)
The effect of hydrogen plasma treatment of iron oxide films on the growth and microstructure of carbon nanotubes (CNTs) by microwave plasma enhanced chemical vapor deposition process has been investigated. Microwave plasma was characterized in-situ using optical emission spectrometer. Morphology of the films was examined by scanning electron microscopy. Structural analysis was carried out by high resolution transmission electron microscopy (HRTEM) equipped with energy dispersive X-ray spectroscopy (EDS) and micro-diffraction attachments. It is found that oxide films without H2 plasma pretreatment or treated for lesser time resulted in CNT films with high percentage of carbonaceous particles and with embedded particles/nanorods distributed discontinuously in the cavity of the nanotubes. The embedded particles were found to be of iron carbide (Fe-C) as confirmed by HRTEM, EDS and micro-diffraction analysis. Experimental observations suggested that the iron oxide particles had poor catalytic action for CNT growth and in-situ reduction of oxide clusters to Fe by hydrogen plasma plays a key role in discontinuous filling of the nanotubes by the catalytic particles.